2006
DOI: 10.1103/physrevb.74.075411
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo approach to island formation during thermal treatment of thin films

Abstract: International audiencetreatment of a polycrystalline thin film deposited on a substrate with no further deposition. Two types of substrates have been studied: a single crystalline substrate with no defects and a single crystalline substrate with defects. We obtain islands which are either flat i.e., with a height which does not overcome a given value or grow in height like narrow towers. The numerical results have been qualitatively compared with experimental data: the fragmentation after thermal treatment of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…28 It should be stressed that the dynamical scaling property of anisotropic two-dimensional systems during coarsening processes has been reported by several authors and demonstrated by computer simulations performed under confined conditions, i.e., in very thin layers or in slab geometries with thicknesses similar to the values of the characteristic correlation distance ͓R͑t͒ =2 / q 1 ͔ in the plane. [31][32][33][34][35] Geometrical confinement effects were not expected in the samples studied here because the film thicknesses ͑Ϸ200 nm͒ are about ten times the largest R͑t͒ values derived from our SAXS curves. Therefore, the present study reveals the validity of the dynamic scaling hypothesis in intrinsic bidimensional coarsening processes.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…28 It should be stressed that the dynamical scaling property of anisotropic two-dimensional systems during coarsening processes has been reported by several authors and demonstrated by computer simulations performed under confined conditions, i.e., in very thin layers or in slab geometries with thicknesses similar to the values of the characteristic correlation distance ͓R͑t͒ =2 / q 1 ͔ in the plane. [31][32][33][34][35] Geometrical confinement effects were not expected in the samples studied here because the film thicknesses ͑Ϸ200 nm͒ are about ten times the largest R͑t͒ values derived from our SAXS curves. Therefore, the present study reveals the validity of the dynamic scaling hypothesis in intrinsic bidimensional coarsening processes.…”
Section: Resultsmentioning
confidence: 84%
“…This finding is in agreement with modeling studies performed by computer simulation, suggesting that the value of kinetic exponent characteristic of isotropic coarsening is also expected for the growth of domains in highly anisotropic systems. 34,35 However, the question that remains unclear is which factor is responsible for the change of the coarsening process from tridimensional to bidimensional by adding 3% of Sb in the undoped SnO 2 matrix. It is well known 28 that grain growth in solid systems is determined by the speed of the grain-boundary motion, which is proportional to the thermodynamic driving force for boundary migration F b and to the boundary mobility M b , the latter parameter depending on the kinetic-controlled transport mechanism.…”
Section: B Kinetic Mechanismmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] A third approach goes by the deposition of a continuous thin xerogel film at the surface of a substrate by sol-gel dip-coating. 30 Through thermal treatment, the continuous thin solid film crystallizes and breaks into several crystals through surface diffusion, [31][32][33] leading to the formation of discrete epitaxial islands on the surface of the substrate. In this case, unlike PVD or CVD, the formation of the epitaxial islands takes place after the deposition of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for our system of N lattice domains, the energy necessary to change crystallographic orientation for domain i with respect to domain j becomes [8] DE 0…”
Section: Numerical Proceduresmentioning
confidence: 99%